A Novel Tubeless Urinary Catheter Protocol Enhanced Recovery After Minimally Invasive Lung Surgery - Wang, Weidong; Xia, Pinghui; Pan, Liang; Xu, Jinming; Lv, Wang; Hu, Jian (Frontiers in Surgery, 2020)
Objectives: Although previous studies have shown the feasibility of non-intubated techniques, it is unknown whether avoiding urinary catheters can enhance recovery. This study aimed to determine whether the tubeless urinary catheter protocol is feasible and beneficial for minimally invasive lung surgery. Methods: Patients were randomized to the control group, completely tubeless group and partially tubeless group. A propensity score-matched (PSM) analysis was performed to balance the nonrandom baseline characteristics. Complications and postoperative recovery were compared. Regression analysis was performed to identify the independent predictors of complications. A nomogram for predicting the risk of non-automatic micturition was constructed and internally validated. Results: 159 patients were enrolled. The incidence of urinary irritation and urinary tract infection (UTI) were significantly lower in the tubeless groups (74.4%vs39.5%, p<0.001; 28.2vs8.6%, p=0.001, respectively). The tubeless group had a higher proportion of 0-degree discomfort (81.5%vs30.8%, p=0.001) and shorter duration of postoperative hospital stay than the control group (4.59vs5.53 days, p<0.001). No difference was observed in terms of urination retention and urinary incontinence between the tubeless group and the control group. After PSM, the advantages of the tubeless group still existed and comparing to the partially tubeless group, the completely tubeless group was of even less UTI and more 0-degree discomfort (18.5%vs0.0%, p=0.019; 96.3%vs59.3%, p=0.002). The tubeless protocol was the only independent protective factor of urinary complications. A nomogram was constructed and showed good predictive ability. Conclusions: The tubeless catheterization protocol led to fewer complications, better compliance and shorter hospital length of stay. The advantages were more significant with the completely tubeless protocol. The utility of our nomogram can assist clinicians in avoiding risks in performing the tubeless protocol.